The Use of 16s RNA AND NODC Gene Sequence in Resolving The Phylogenetic Relationship of Rhizobia Associated With Paraserianthes falcataria (L.) Nielsen Plant - Prana, Titik K.; Sone, Teruo; Nakagawa, Hiroko Kawasaki; Yokota, Atsushi; Seki, Tatsuji; Tomita, Fusao (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2004)
Studies on genet ic position of several iso lates liv ing symbiot i a lly on ParaseriCllltli esfalcalaria have been carried out using amplification and se uenc ing tec hni ques of 16S rDNA and specific gene fo r nodulation (/lode) . The